COMPARISON OF STATE-TRAIT ANXIETY LEVELS OF STUDENTS LIVING WITH THEIR FAMILIES AND STUDENTS WHO LIVE SEPARATELY FROM THEIR FAMILIES - Recep CENGIZ; Emrah SERDAR; Bilge DONUK (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The purpose of this study is to compare anxiety levels of the college students who are living with or separated from their families. The sample group of the study consist of 343 males and 104 females, 447 in total, in the academic year of 2015-2016 at Bartın University. In the research, Spielberger State-Trait Anxiety Inventory has been used. In order to determine that if the data had a normal distribution ratio or not, Shapiro-Wilks normality test has been conducted; and as a result, after it has been seen that the data was suitable for non-parametric test conditions, Mann-Whitney U and Kruskal-Wallis tests have been carried out in order to determine the significant differences (p<0,05). There has not been found any major differences between the state-trait anxiety levels of the students living with and separated from their families based on their genders. However, female participants have made higher points in proportion to male participants. There has not been found any significant differences between the state-trait anxiety levels of the students living with and separated from their families. However, participants living separated from their families have made higher points in proportion to the participants living with their families. There has not been found any significant differences between the state-trait anxiety levels of the participants based on their ages. However, state-trait anxiety points of the participants aged between 23-25 are higher than the state-trait anxiety points of the participants with other age ranges. As a result; it has been determined that the state-trait anxiety levels of the students living separated from their families have been higher than the participants living with their families.